WAKAF DI SAUDI ARABIA DAN MESIR (TINJAUAN MANAJEMEN DAN TERAPAN WAKAF PRODUKTIF) - Muhsan, Muhsan (Al-MAJAALIS, 2013)
Waqf is a source of significant economic Muslims. Good management of waqf can be an effective source of financing in various vital sectors such as the construction of the ummah needs education facilities, places of worship and health facilities such as hospitals, etc. In many Islamic countries waqf management policies are handled directly below a certain department. For example, in Saudi Arabia and Egypt, and this paper will discuss the management of endowments in the two countries. The discussion begins with an explanation of the function and usability perspective endowments Islamic normativity later implementation in several countries and ended with the conclusion that recommends that the successful utilization of endowments depends on a good management system. The authors hope the management knows her endowments of the two countries above may contribute to the development of motivation more productive endowments for other countries. Keywords : Manajemen, Wakaf produktif , Saudi Arabia, Mesir .